Analisis Perlakuan Akuntansi Atas Selisih Kurs Dalam Transaksi Mata Uang Asing PT Industri Jamu Dan Farmasi Sido Muncul Tbk (Jurnal Kendali Akuntansi, 2024)
This research examines the accounting treatment of exchange rate differences and foreign currency transactions at PT Industri Jamu and Farmasi Sido Muncul Tbk, focusing on understanding the Financial Accounting Standards (FAS), particularly FAS No. 10. The analysis is conducted on the company's consolidated financial statements, exploring the impact of foreign exchange transactions, determination of functional currency, and foreign exchange rate risk. The results indicate that the company has adhered well to FAS provisions in presenting information regarding exchange rate differences and foreign currency transactions.